KETERLIBATAN ORANG MUDA KATOLIK DALAM KARYA KARITATIF DI GEREJA PAROKI ST.CORNELIUS MADIUN - Elisabet Pipit Wahyunita; Ola Rongan Wilhelmus (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Charity of the Church is a social activity developed continuously by the Church to respond human sufferings. This action needs an active participation of the people in the Church, including adults. In fact, the young involve less in charity works of the Church due to some challenges such as laziness and technology development which has consumed a lot of their times. This study applied a qualitative research approach. Qualitative research is a kind of research which focuses in understanding and analyzing human attitude, opinion, emotion and behavior about a specific social phenomenon being studied. The objectives of this research are to analyze the understanding of adults about charity works of the Church, how far they get involved in charity works of the Church, and the efforts taken by the adult themselves, their parents and the Church to make the young people to be more involved in charity works of the Church. To counter such challenges, there have been particular efforts taken by the catholic youth themselves, their families and the Church to help catholic youth people to be more involved in charity works of the Church. Such efforts were including the effort to develop a good communication with their friends who have involved in charity works and both parents and the Church tried to give more motivation to the young to involve more in the Church charity works.